Representasi Hindu dan Masyarakat Plural dalam Serial Gagaklodra - Heri Kusuma Tarupay (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2025)
In 1935–1937, Gagaklodra traveled to India to observe Hinduism as an integral part of the way of life of its people. The results of his journey in India, including his encounters with criminal figures and his efforts to address various issues there, were later conveyed to his readers in the Indies. This paper conducts a textual analysis of Gagaklodra’s serials set in India. Hinduism becomes the central focus of this study in order to examine its position within the plural society imagined by Gagaklodra. Hinduism and its place within the plural society envisioned by Gagaklodra represent a way of living together that remains relevant and necessary to be practiced in Indonesia today.